Нові гени, що контролюють продукцію антибіотиків фосфогліколіпідного ряду - Осташ, Б.О.; Горбаль, Л.О.; Забуранний, Н.В.; Лопатнюк, М.М.; Мутенко, Г.В.; Рабик, М.В.; Громико, О.М.; Осташ, І.С.; Уокер, С.; Федоренко, В.О. (Фактори експериментальної еволюції організмів, 2015)
Aims. To identify novel genes for biosynthesis of moenomycin-like natural products in actinomycetes, and genes that
control their production at transcriptional and posttranscriptional levels. Methods. Bionformatic genome mining was
combined with experimental verification of selected genes; gene knockouts and erexpression studies were used for the
latter. Results. A genetic network putatively controlling the production of moenomycins by Streptomyces ghanaensis
ATCC14672 is described. Involvement of several genes from this network was verified experimentally. Gene cluster for
biosynthesis of biosynthesis of putative phosphoglycolipid natural product was identified in the genome of Actinoplanes
teichomyceticus, and this cluster features both novel genetic architecture and novel genes for phosphoglycolipid
biosynthesis. Conclusions. The obtained data create a working ground for development of moenomycin overproducers
and generation of producers of novel moenomycins.
Keywords: Streptomyces, antibiotics, phosphoglycolipid, moenomycin.